Optimal Design of Specimens for Pure Shear Tests of Sheet Metals - G. Socha (Engineering Transactions, 1994)
A new type of simple specimens for experimental testing of plastic properties of sheet metals under pure shear conditions is proposed and optimized. The objectives of optimal design require possible uniformity of the shear stress distribution and possibly small effects of stress components other than σ12. Computations have been performed numerically with the use of two FEM systems for 4 types of specimens, which have been used in experimental tests for determining the yield shear stress Q of sheet metals. Conventional shear stress-displacement diagrams obtained in these tests have been compared with the results of numerical calculations.